Terapi kognitif untuk menurunkan kecemasan mendapat penilaian negatif pada individu dewasa - Frida Tia Rahma (Universitas Muhammadiyah Malang, 2022)
Fear of Negative Evaluation (FNE) is a condition in which individuals are afraid to get negative evaluations from others, stay away from situations related to evaluation, and expect others to evaluate negatively. This is in accordance with the subject where she experiences anxiety when interacting with strangers, expresses opinions in many people's forums and finds it difficult to interact with men. This condition is caused her belief will be judged negatively by others. The assessment was carried out using interviews, observation. Graphic tests (Draw a Person, BAUM, House Tree Person) and Sack’s Sentences Completion Test. Cognitive therapy with cognitive restructuring are given yo reducing anxiety that is judged negatively by others. The results show that the subject can realize that her thoughts are not always correct, so she no longer focuses on the negative judgments of others